Isolasi Dan Identifikasi Terpenoid Fraksi Heksan Daun Premna serratifolia L. Menggunakan GC-MS - Ricky Midi Candra; Isnindar Isnindar; Sri Luliana (Journal Syifa Sciences and Clinical Research, 2023)
Buas-buas (Premna serratifolia L.) is a plant that belongs to the Verbenaceae family. Terpenoid compounds that exist in buas-buas plants have bioactivity as medicine. Terpenoid compounds are soluble compounds in n-hexane. The purpose of this study was to isolate and identify the terpenoid compounds contained in the n-hexane fraction of buas-buas leaves using the GC-MS method. The buas-buas leaves were macerated with 96% ethanol solvent and then fractionated using a separating funnel with n-hexane as solvent. The n-hexane fraction of buas-buas leaves was isolated using column chromatography with a gradient mobile phase combination of n-hexane and ethyl acetate, then identified using the GC-MS instrument. The terpenoid compounds found in the n-hexane fraction of buas-buas leaves are estimated to be neophytadiene; 3,7,11,15-tetramethyl-2-hexadecen-1-ol; and 2 hydroxy-4a,5-dimethyl-3-(prop-1-en-2-yl) octahydronaphthalen-1-(2H)-one.